2016
DOI: 10.1111/cen.13075
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary apoplexy – bespoke patient management allows good clinical outcome

Abstract: In pituitary apoplexy patients managed conservatively or surgically, there is good recovery of visual symptoms but not endocrine function. Patients should be managed on a case-by-case basis based on the severity of symptoms at presentation, progression of disease and surgical expertise available. Further prospective studies using the PAS are required to determine its usefulness in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 37 publications
3
40
2
7
Order By: Relevance
“…In the former condition, hypopituitarism is frequently permanent, while in the latter one recovery of endocrine function can be obtained by debulking of the pituitary mass [63, 106]. However, in terms of endocrine outcome, some studies showed that pituitary hormones deficiencies consequent to pituitary apoplexy infrequently recover and the persistence of hypopituitarism seems to be not related to management modalities [4, 96, 99, 101, 107]. …”
Section: Prognosismentioning
confidence: 99%
“…In the former condition, hypopituitarism is frequently permanent, while in the latter one recovery of endocrine function can be obtained by debulking of the pituitary mass [63, 106]. However, in terms of endocrine outcome, some studies showed that pituitary hormones deficiencies consequent to pituitary apoplexy infrequently recover and the persistence of hypopituitarism seems to be not related to management modalities [4, 96, 99, 101, 107]. …”
Section: Prognosismentioning
confidence: 99%
“…To assess for the effect of dichotomizing, the time from symptom onset to surgery-as performed in other studiesthe time variable was dichotomized at 1, 2, 3, 5, 7, 10, and 14 days, most of which have been previously assessed as a dichotomization time in other studies. [10][11][12][13][14][15] Odds ratios of improved vision based on each dichotomized value were determined by univariate logistic regression, as shown in ►Fig. 3.…”
Section: Assessment Of Timing Of Surgery and Visual Outcomesmentioning
confidence: 99%
“…Although impairment of visual fields or visual acuity has necessitated urgent decompressive surgery in most series (61), the optimal management strategy is still controversial. Potential approaches include immediate (within days) or delayed (within weeks) surgery or conservative management (61,62,63,64,65,66,67). The safety of delayed surgical intervention remains uncertain.…”
Section: Pituitary Tumour Apoplexymentioning
confidence: 99%
“…Bujawansa et al (64) in a series of 55 patients (23 had immediate surgery (within 7 days), 10 delayed surgery and 22 managed conservatively) showed rates of improvement to visual field defects and cranial nerve palsies 60-80% and 92-100% respectively, with no significant differences between treatment strategies. Giritharan et al (65) reported on 31 patients (11 had emergency surgery (within 7 days), 9 delayed surgery and 11 conservative management); all patients, except one in the conservatively managed group, had improvement or resolution of visual defects, while complete resolution was seen in 70, 75 and 71% of the immediate surgery, delayed surgery and conservatively managed patients, respectively. Selection bias must be considered when interpreting these data, as cases with milder symptoms at presentation are more often managed with delayed surgery or conservatively (61,62,63,64,66).…”
Section: Pituitary Tumour Apoplexymentioning
confidence: 99%
See 1 more Smart Citation